Implementation Blue Accounting For Economic and Environmental Sustainability (Case Study of Salt Ponds at Talise Beach, Palu City) - Ulva, Ulva; Yamin, Nina Yusnita; Indriasari, Rahayu; Parwati, Ni Made Suwitri; Yuniar, Latifah Sukmawati (UNIVED Press, 2026)
Blue accounting, which integrates accounting principles with sustainability aspects, provides a holistic perspective on natural resource and environmental management. This study explores the application of blue accounting in the salt ponds of Talise Beach, Palu City, a coastal marine ecosystem rich in blue economy potential. Using qualitative methods, this study involved in-depth interviews, observations, and document analysis to examine blue accounting practices from a sustainability perspective. Interview data were analyzed thematically using the NVivo application, based on ecophenomenology theory to understand the interaction between humans (salt farmers) and the natural environment. The results show that salt farmers in Talise Beach live in a complex and profound interaction with their environment, especially seawater, land, and weather conditions. Salt farmers strive to manage natural resources effectively to improve production quality and yields, while facing evolving ecological and technological challenges. The salt production process still relies heavily on natural cycles and simple technology. Therefore, the production and quality of salt produced are also highly dependent on natural cycles. The quality of salt will impact its economic value and usefulness. This study provides a rich understanding of how local practices can reflect blue accounting principles, highlights the ecological and technological challenges faced, and offers insights for the development of a more holistic blue economy sustainability model.